2019
DOI: 10.1128/aac.02093-18
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA-Dependent RNA Polymerase Inhibitor 7-Deaza-2′- C -Methyladenosine Prevents Death in a Mouse Model of West Nile Virus Infection

Abstract: West Nile virus (WNV) is a medically important emerging arbovirus causing serious neuroinfections in humans and against which no approved antiviral therapy is currently available. In this study, we demonstrate that 2′-C-methyl- or 4′-azido-modified nucleosides are highly effective inhibitors of WNV replication, showing nanomolar or low micromolar anti-WNV activity and negligible cytotoxicity in cell culture. One representative of C2′-methylated nucleosides, 7-deaza-2′-C-methyladenosine, significantly protected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…In the HCV subgenomic replicon system, dasabuvir inhibits genotype 1a and 1b replicons with EC 50 values of 7.7 and 1.8 nM, respectively [30]. In our in vitro assays, dasabuvir had a micromolar EC 50 , which was comparable to other small molecule inhibitors that showed effectiveness in laboratory animals infected with VBFs [25][26][27]39,40]. The antiviral activity of dasabuvir was demonstrated regardless if applied before infection, at the time of infection, or post-infection ( Figures 2B and 4, Supplementary Figure S1).…”
Section: None Of the Pdb Non-nucleoside Co-crystalized With Flavivirusupporting
confidence: 51%
See 2 more Smart Citations
“…In the HCV subgenomic replicon system, dasabuvir inhibits genotype 1a and 1b replicons with EC 50 values of 7.7 and 1.8 nM, respectively [30]. In our in vitro assays, dasabuvir had a micromolar EC 50 , which was comparable to other small molecule inhibitors that showed effectiveness in laboratory animals infected with VBFs [25][26][27]39,40]. The antiviral activity of dasabuvir was demonstrated regardless if applied before infection, at the time of infection, or post-infection ( Figures 2B and 4, Supplementary Figure S1).…”
Section: None Of the Pdb Non-nucleoside Co-crystalized With Flavivirusupporting
confidence: 51%
“…Plaque assays were performed in Vero cells (for ZIKV and WNV titers) or in the PS cells (to determine TBEV titers) as described previously [23][24][25]. The obtained viral titer values were recalculated to percentages of viral titer inhibition, applied to constructing the dose-response and inhibition curves, and used to calculate the 50% effective concentration (EC 50 ).…”
Section: Plaque Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…S1. Some of the uridine analogues listed above have been investigated as inhibitors of viral polymerases (Kumaki et al 2011;Eyer et al 2019;Arup et al 1992;Lauridsen et al 2012). The 2'-O-methyluridine triphosphate is of particular interest, since it has been demonstrated that 2'-O-methyl nucleotides are resistant to removal by the 3'-exonuclease found in coronaviruses (Minskaia et al 2006).…”
Section: Selection Of Candidate Nucleoside Triphosphates For Coronavimentioning
confidence: 99%
“…The limitations of targeting cell death in reversing WNV disease, include the timing, infection severity, and treatment dosage. For example, timing of such treatments is very critical-if too late, the damage cannot be prevented or reversed [66].…”
Section: Targeting Cell Death Factors For Treatment Of Wnv Infectionmentioning
confidence: 99%